Acute Acquired Comitant Esotropia (AACE) – post COVID-19 home confinement - T.G., Aida; C.S., Syarmilla; Mustapa, Rossaidah; A. A., Aznor Azwan; Abdul Rahim, Muhammad Afzam Shah (2023)
AACE is a relatively rare form of strabismus characterized by a sudden onset of concomitant esotropia with diplopia. A 7-year-old boy presented to the Ophthalmology Department, HRPZ II, Kota Bharu with acute onset of diplopia. Two days before the presentation, his parents noted crossed eyes when he woke up and dancing eyes. He had no history of recent infections or physical or psychological stress. In the past 2 months, he used a tablet approximately 8 hours a day. His best corrected visual acuity (BCVA) was 6/12 on RE and 6/18 on LE eye. Stereopsis was not detectable by the Lang test.Manifest esotropia was 20 prism diopters (PD) at both far and near distances in all positions of gaze. The cycloplegic refraction was RE +0.75/-1.00 x 20 (6/7.5) and LE +1.50 / -1.00 x 165 (6/7.5) Ductions and versions were full. Neurologic evaluation and brain magnetic resonance imaging (MRI) under sedation were unremarkable. Full time glasses was prescribed, although other treatment options such as prisms and topical cycloplegics were discussed. A 22-year-old girl presented to the Ophthalmology Department, HRPZ II, Kota Bharu with acute onset of diplopia. She is studying on statistic course and spend many hours on computers. She had no history of recent infections or physical or psychological stress. The patient reported an intense use of the computer for more than 8 hours a day. She had worn any glasses yet. Her BCVA was 6/6 in both eyes. On alternate cover test, the manifest esotropia was 25 PD at both far and near distances in all positions of gaze. Ductions and versions were full, with no pattern strabismus. The cycloplegic refraction was RE -2.00/-0.25 X 180 and LE +1.00/-1.00 X 180. Neurologic evaluation and MRI were normal. Home confinement during covid-19 appeared to cause an increasing total hours of screen time and the number of consecutive minutes/hours without visual breaks should be recommended to prevent AACE.